Pengaruh Model Pembelajaran Problem Based Learning Berbantuan E-LKPD terhadap HOTS Literasi Siswa pada Materi Kesetimbangan Kimia - Rumapea, Sri Anugrah Cristina; Suyanti, Retno Dwi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to analyze whether the literacy HOTS of students taught with the E-LKPD-assisted Problem Based Learning (PBL) model is higher than the literacy HOTS of students taught using the conventional model. The population of this study is class XI of SMA Negeri 2 Medan which consists of 12 classes. The research sample was 36 students in grades XI Sativa and XI Pluto. The test instrument was 24 valid items with an r11 value of 0.873. The hypothesis test used the right-hand t-test with the results of the study obtained a tcal value of > ttable (7.481 > 1.994). This means that Ha is accepted and H0 is rejected, which means that the HOTS of student literacy using the Problem Based Learning (PBL) model assisted by E-LKPD media is higher than the HOTS of student literacy by using the conventional model on chemical equilibrium material, with an N-Gain value in the experimental class of 0.80 (80%), and an N-Gain value in the control class of 0.65 (64.94%). Furthermore, the most developed aspect of literacy HOTS is C5 level reasoning with a percentage of 87%. These findings prove that E-LKPD-assisted PBL is effective in improving HOTS-based chemical literacy in chemical equilibrium materials.